A model free dissolved oxygen controller for industry effluent using hybrid variables measuring technique - P. Kingston Stanley; Sanjeevi Gandhi A.; D. Abraham Chandy (Institute of Advanced Engineering and Science, 2019)
The present scenario of the world relays on water scarcity, enormous amount of water is needed for people but the world has pollution which makes a great effect. Water is polluted due to various reasons such as industrial waste, sewage, and global warming and oil pollution and mainly polluted due to industrial effluent waste water. The main objective of this paper is to control the dissolved oxygen of the industrial waste water by measuring turbidity and dissolved oxygen (DO). Turbidity is measured through the intensity of the light through the medium in Nephelometric unit (NTU) and dissolved oxygen is measured in PPM through amperometic electrode method. The controller is designed to improve the quality of the effluent water through the aeration process. The very low concentration of dissolved oxygen (DO) level is too harmful to the aquatic ecosystem and it pollutes the water to the maximum extent. This measurement method of turbidity has an enhanced idea which processed with the software and it is monitored. The controller is designed as such with the condition of inverse proportionality of water turbidity and dissolved oxygen, which contributes an additive advantage to the concept design.